Pediatric Sepsis: Clinical Markers - Szima, S.; Balazs, G.; Elek, N.; Dahlem, P. (Journal of Child Science, 2017)
Pediatric sepsis can be caused by infection agents such as viruses, bacteria, protozoa, or their toxins. Clinical features cover a remarkably wide spectrum. Early recognition of the disease and prompt initiation of therapy substantially improve mortality and the outcome of potential complications. After an initial phase of very mild symptoms, the spread of microbes or toxins in the bloodstream presents as septic shock through vasoregulatory disturbance, absolute or relative intravascular volume loss, and consequential tachycardia and hypotension. The most common accompanying symptom is fever. In physical examination, features such as altered mental status, excess respiratory effort, tachycardia, and prolonged capillary refill time are present at an early stage of the disease. Laboratory tests for the assessment of early stage severity and subsequent monitoring of treatment efficacy include point-of-care arterial blood gas analysis and lactate assay. In early stage disease, it is imperative to promptly start adequate antimicrobial and supportive treatment once bacterial cultures have been taken. Despite the availability of a wide range of laboratory and imaging tests today, diagnosis and severity assessment of sepsis still primarily rely on medical history and clinical examination. In light of this, it is possible for trained care providers to detect the early signs of a septic child during repetitive physical examinations. This is still the mainstay of diagnosis and can provide in all care settings a significant reduction in therapeutic delay; this, in turn, helps to reduce sepsis-related mortality and morbidity.
Keywords: sepsis; physical examination; evaluation; septic shock; children; infection; review